Community involvement in MDP 301 microbicide trial in Masaka: Successes and failures - HEPS (HEPS-Uganda Policy Briefing Series, 2010)
The MDP 301 microbicide trial used multiple approaches at the Masaka site to mobilise and sensitise the community, get feedback, share information, and communicate the final trial results. While this broad approach contributed to the success of the trial, a survey conducted early 2010 found no evidence that civil society advocacy groups were invited to contribute to the trial’s design and implementation. By outlining the key successes and failures of the trial’s community involvement initiatives, this brief highlights the need for HIV prevention research in general to follow good community participatory practice guidelines by nurturing local advocates from the civil society to partner with the investigators in the conduct of research.